Family Dynamics and Young Adults’ Well-Being: The Mediating Role of Sibling Bullying - Plamondon, Andréanne (Journal of interpersonal violence, 2021)
Although a common form of family violence, sibling bullying is often viewed as harmless by families and society. Consequently, it has not received as much attention in research compared with peer bullying or other types of family violence, such as interpartner violence, child abuse, and elder abuse. Considering that sibling relationships have lasting effects on children’s development, this retrospective study focused on the antecedents and outcomes of sibling bullying. Grounded in family system theory and social learning theory, it explored whether sibling bullying during childhood and adolescence mediated the relationship between negative family dynamics (i.e., sibling rivalry, interparental hostility, and parental hostility) and young adults’ well-being (i.e., sense of competence, internalized problems, self-esteem, and satisfaction with life). Data from 216 respondents were analyzed using structural equation modeling. Results revealed that young adults who reported higher levels of sibling rivalry and interparental hostility were more likely to be victims of sibling bullying. In turn, sibling bullying was associated with lower sense of competence, self-esteem, and life satisfaction, as well as more internalized problems. Parents’ hostile behaviors toward their children were not associated with sibling bullying but were negatively associated with well-being in early adulthood. Our work underlines the importance of harmonious family dynamics and the need for sibling bullying to be taken more seriously by parents and family members. From a clinical point of view, our findings suggest that clinicians and human service workers should adopt a family-level approach when trying to reduce sibling bullying and its negative outcomes by educating parents about the interdependence of family relationships.